Multistage multiantigen heterologous prime boost vaccine for Plasmodium knowlesi malaria provides partial protection in rhesus macaques. - Rogers, W; Baird, J; Kumar, A; Tine, J; Weiss, W; Aguiar, J; Gowda, K; Gwadz, R; Kumar, S; Gold, M; Hoffman, S (2001)
A nonhuman primate model for malaria vaccine development allowing reliable, stringent sporozoite challenge and evaluation of both cellular and antibody responses is needed. We therefore constructed a multicomponent, multistage DNA vaccine for the simian malaria species Plasmodium knowlesi including two preerythrocytic-stage antigens, the circumsporozoite protein (PkCSP) and sporozoite surface protein 2 (PkSSP2), and two blood stage antigens, apical merozoite antigen 1 (PkAMA1) and merozoite surface protein 1 (PkMSP1p42), as well as recombinant canarypox viruses encoding the four antigens (ALVAC-4). The DNA vaccine plasmids expressed the corresponding antigens in vitro and induced antiparasite antibodies in mice. Groups of four rhesus monkeys received three doses of a mixture of the four DNA vaccine plasmids and a plasmid encoding rhesus granulocyte-monocyte colony-stimulating factor, followed by boosting with a single dose of ALVAC-4. Three groups received the priming DNA doses by different routes, either by intramuscular needle injection, by intramuscular injection with a needleless injection device, the Biojector, or by a combination of intramuscular and intradermal routes by Biojector. Animals immunized by any route developed antibody responses against sporozoites and infected erythrocytes and against a recombinant PkCSP protein, as well as gamma interferon-secreting T-cell responses against peptides from PkCSP. Following challenge with 100 P. knowlesi sporozoites, 1 of 12 experimental monkeys was completely protected and the mean parasitemia in the remaining monkeys was significantly lower than that in 4 control monkeys. This model will be important in preclinical vaccine development.